Energy allocation in relation to spawning and overwintering of a diadromous Puyen (Galaxias maculatus) population in the southernmost limit of the species distribution - Boy, Claudia Clementina; Pérez, Soledad Analía; Fernández, Daniel Andrés; Calvo, Jorge; Morriconi, Elba Rosa (Polar Biology)
A population of Galaxias maculatus, a native species in southern South America, living under cold-temperate conditions (0°C water temperature with an ice layer covering the stream during the coldest days) and 7 h of light in winter undergoes high energetic demands in the population studied. We analyzed the energy density of gonads, liver, fat and muscle, through calorimetry for the first time in this species. Energy density of fat and liver were extremely high (34.77-56.52 and 29.54-40.77 kJ/g respectively). While perivisceral fat reserves were likely used for overwintering, liver and muscle reserves were used for reproduction. High energy densities were also found in gonads (27.76 kJ/g in ovaries and 25.84 kJ/g in testes). High investment in gonads of males suggests the presence of sperm competition. The temporal variation of the energy content of gonads, liver, fat and muscle indicates that the allocation of energy occurs by the internal transference of energy between organs and tissues. Fil: Boy, Claudia Clementina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Pérez, Soledad Analía. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Fernández, Daniel Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Calvo, Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Morriconi, Elba Rosa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina